Age, Gender, and BMI Distribution in Cholelithiasis Patients: A Study in Sylhet (Jalalabad Medical Journal, 2026)
Cholelithiasis, a common gastrointestinal condition, is influenced by various factors, including age, gender, BMI, and genetic predisposition. This study aimed to assess the distribution of age, gender and BMI among patients diagnosed with cholelithiasis in Sylhet. A cross-sectional study was conducted from January to June 2022 at Popular Medical Centre and Hospital in Sylhet, involving 200 cholelithiasis patients confirmed through imaging studies. Data were collected through face-to-face interviews, physical examinations, and medical records review. Variables such as age, gender, BMI, the ABO blood group, and family history of gallbladder disease were analysed using descriptive statistics. Among the 200 patients, females (65.5%) were more affected than males (34.5%), with a male-to-female ratio of 1:1.9. The mean age was 45.10±14.30 years, with the highest prevalence in the 48-57 years age group (25.5%). Most patients (50%) had a BMI within the normal range (18.5-24.9), while 46% were underweight (